Upaya Meningkatkan Hasil Belajar Matematika Melalui Strategi Pembelajaran Berbasis Masalah Di Kelas V SDN 02 Sitiung Tahun Pelajaran 2021/2022: Efforts to Improve Mathematics Learning Outcomes through Problem-Based Learning Strategies in Class V SDN 02 Sitiung For the 2021/2022 Academic Year - MISMARNI MISMARNI (International Journal of Technology Vocational Education and Training, 2022)
The data of this research is in the form of information about the data on the results of the actions obtained from the observations of teacher activities, student activities, initial tests and final tests of learning. The research subjects were students of class V, totaling 13 people. The results of observations on teacher activities achieved good success and in cycle 2 increased to achieve very good success. While the student activities in cycle 1 achieved good success and cycle 2 achieved very good success. Before the implementation of learning through SPBM, a test was carried out with the average score obtained by students of 54. After learning through SPBM the average value of students in cycle 1 increased to 68. However, learning was still continued to cycle 2 because there were still students who had not reached the standard of mastery learning . Learning ends in cycle 2 because students have reached the standard of completeness that has been set and the average value of students has increased from cycle 1 to 81.